Safety for American Indian Women - December Maxwell; Sarah Robinson (Advances in Social Work, 2020)
American Indian/Native American (AI/NA) women are disproportionately affected by intimate partner violence (IPV). The Violence Against Women Reauthorization Act (VAWA) of 2013 included new provisions under the Title IX Safety for Indian Women. This act created funding for the implementation of modern criminal justice structures allowing tribal governments to prosecute non-Indian perpetrators. Although this piece of legislation is meant to address the high prevalence of gender-based violence perpetrated against AI/NA women, it has not been analyzed using indigenous or feminist perspectives. A policy analysis model was developed, incorporating indigenous values, feminist perspectives, tribal critical race theory, and social construction and historical contexts to examine Title IX's goals, social values, and outcomes from an indigenous perspective. The analysis reveals the intentions of Title IX to promote indigenous values of empowerment and interdependence but fails to account for the historical marginalization of AI/NA people and the tendency of AI/NA women to distrust law enforcement. Although Title IX did create cultural change and enhance acknowledgment of IPV improvements are needed to make a more indigenous-focused, feminist-based policy. These suggestions include providing access to culturally sensitive law enforcement approaches for AI/NA women, accounting for historical factors, and creating a standardized pathway for prosecution, which incorporates feedback from tribal members.